TREND OF RESEARCH OF THE MICROBIOME OF MUNICIPAL SOLID WASTE LANDS «SHYMKENT-KOKHYS» (Eurasian Journal of Ecology, 2025)
One of the problems causing the environmental crisis in the country and at the global level are industrial and household waste. According to statistical data, Kazakhstan is accumulating 4.6 million tons (t) of solid household waste, of which 2.8 million tons are waste produced by various enterprises and industries of the country. 71% is household waste, 14.6% is industrial waste, 10% is street waste, 2% is market waste. One way to rationally organize the destruction and bioutilization of household waste is to find a source of waste-free technology. According to the study conducted by us it was established that on the territory of the Shymkent garbage landfill titer of microorganisms studied groups consists of 1-10 g in soils taken around the debris. The titer of microorganisms in the soil horizon was high at a depth of 20-30 cm, titer is 109 kl/ml. The soil microbiome structure obtained around the Shymkent-Garbage Landfill consists of actinomycetes, micromycetes, heterotrophic bacteria, nitrifying, nitrogen-fixing bacteria, enterobacteria, and algae and protozoa. Among the heterotrophic bacteria present in the microflora are members of the family Bacillus sp., Brevibacterium sp., Pseudomonas sp., Micrococcus sp., nitrifying bacteria include Nitrospira sp., nitrogen-fixing bacteria and Enterobacteria, Klebsiella sp, Streptococcus sp., Staphylococcus sp., and from microscopic fungi there are members of the genus Mucorales, Aspergillus and Fusarium.Keywords: Microorganisms, microbiome, Salmonella, Klebsiella, Streptococcus, Staphylococcus, municipal solid waste, landfills